Further Data on Ortho- and Clinopyroxenes from the Pyroxene Granulites of Swat-Kohistan, Northern Pakistan - Jan, M. Qasim (Journal of Himalayan Earth Sciences, 1983)
Microprobe analyses of pyroxenes from the pyroxene granulites of Swat-Kohistan are similar to their wet chemical analysis and the two sets of analysis yield similar temperature estimates. The pyroxenes are exsolved, but the exsolved pyroxene is similar chemistry to its corresponding principal pyroxene, suggesting the attainment of physico-chemical equilibrium. The Mg/(Mg + Fe") ratios for the coexisting pyroxenes have been plotted and the implications of granulite facies metamorphosed noritic teases in the amphibolite belt of Kohistan discussed.